Pengaruh Media Exposure Tehradap Pengungkapan Corporate Social Responsibility Perusahaan Manufaktur Terdaftar di BEI - Sparta, Sparta; Rheadanti, Desak Kadek (EQUITY, 2019)
Social and environmental responsibility becomes one of the components of corporate disclosure listed on Indonesia Stock Exchange (BEI). This study examines the factors that influence the disclosure policy of social and environmental responsibility to manufacturing companies on BEI by expanding disclosure items. Factors suspected to affect social and environmental responsibility disclosure policies are media exposure, firm size, profitability and leverage. The research sample is a manufacturing company that discloses social and environmental responsibility in the period 2013-2015. The number of sample companies is 31. The number of observations used is 93 observations. The disclosure policy of social and environmental responsibility is measured by the disclosure index. This index is measured by the disclosure item in the Reporting Guidelines contained in General Repoting Initiatives (GRI). Hypothesis testing is done by multiple regression analysis. The test results fail to prove the effect of media exposure, firm size and profitability on the disclosure of social and environmental responsibility.